The optimal use of chlormethine gel for mycosis fungoides: an expert consensus from Germany, Austria and Switzerland (DACH region) - Assaf, Chalid; Booken, Nina; Dippel, Edgar; Guenova, Emmanuella; Jonak, Constanze; Klemke, Claus-Detlev; Nicolay, Jan Peter; Schlaak, Max; Wobser, Marion; Trautinger, Franz (Journal der Deutschen Dermatologischen Gesellschaft, 2022)
Background In Europe chlormethine gel is licensed for the management of patients with mycosis fungoides of all stages. However, the optimal regimen regarding frequency and dosing as well as combination and maintenance therapy is not well established. Methods Ten experts experienced in research and management of cutaneous T-cell lymphomas from Germany, Austria, and Switzerland (DACH region) were asked in written form to report on indication for chlormethine gel, frequency of use, monitoring, concomitant therapies, adverse effects, combination therapies in later stages of the disease, maintenance therapy, and adherence to this therapy for mycosis fungoides. The structured answers were discussed in a consensus conference and recommendations were developed. Results Essential for therapy with chlormethine gel is an individualized and symptom-oriented management. Because of the lack of systemic resorption of topically administered chlormethine gel, systemic adverse events are unlikely. An allergic or irritative-toxic contact dermatitis is common but manageable with adaptation of the regimen, interruption of administration, and symptom-specific supportive measurements. A step-up initial approach with application of chlormethine gel every other day is associated with a better tolerability, especially if it is alternated with topical corticosteroids. Conclusions The use of chlormethine gel in the management of mycosis fungoides is often limited by a concomitant contact dermatitis. An adequate therapeutic regimen and the management of adverse effects can preclude an unnecessary withdrawal of therapy so that more patients can benefit from this treatment option.
Gesehen am 13.02.2024